PORPHYSOMES-A PARADIGM SHIFT IN TARGETED DRUG DELIVERY - Menon, Revathy B.; S., Lakshmi V.; U., Aiswarya M.; Raju, Keerthana; Nair, Sreeja C. (International Journal of Applied Pharmaceutics, 2018)
A novel drug delivery system is the one that ensures optimum dose at the right time, at the right location. Porphysomes are among those drug delivery systems. Porphysomes are a means of vesicular drug delivery systems. They are liposome-like structures composed completely of porphyrin lipid. The porphysomes encapsulates the active medicament in vesicular structure. They are having an aqueous core which can be loaded with the medicament. They have the capacity to destroy the disease tissues. They absorb the heat in the near infrared region and release this heat to destroy the diseased tissues. Porphysomes are having immense applications in the field of positron-electron therapy (PET), photoacoustic imaging, photothermal therapy etc. This review article discusses regarding the Porphysome-the drug delivery system, its advantages and disadvantages, composition, method of preparation, applications and various aspects related to the porphysomal drug delivery.